Enhancing thermoelectric performance of solutionpProcessed polycrystalline SnSe with PbSe nanocrystals - Liu, Yu; Lee, Seungho; Fiedler, Christine; Spadaro, Maria Chiara; Chang, Cheng; Li, Mingquan; Hong, Min; Arbiol, Jordi; Ibáñez, Maria (Chemical Engineering Journal)
There is a growing interest in cost-effective polycrystalline SnSe-based thermoelectric (TE) materials, which are able to replace the high performance but mechanically fragile and costly single-crystalline SnSe. In this study, we present a low-temperature solution-based approach to produce SnSe-PbSe nanocomposites with outstanding TE performance. Our method involves combining surfactant-free SnSe particles with oleate-capped PbSe nanocrystals in specific ratios, followed by thermal annealing and consolidation using spark plasma sintering. These nanocomposites are characterized by distinct compositional and structural properties that significantly impact their transport properties. In particular, the addition of oleate-capped PbSe nanocrystals results in: i) a reduction in the electrostatically adsorbed Na at the surface of the SnSe particles; ii) a reduction of Sn vacancies due to alloying with Pb; iii) an increase in grain boundary density; and iv) the formation of PbSnSe secondary phases. Notably, the SnSe-2.5 %PbSe nanocomposites demonstrate a 30 % decrease in thermal conductivity compared to that of the SnSe matrix. This reduction contributes to a maximum figure of merit (zT) of 1.75 at 788 K with a high average zT value of ca. 1.2 in the medium temperature range of 573–773 K. These values represent one of the highest reported in polycrystalline SnSe materials, showcasing the potential of our fabricated SnSe-PbSe nanocomposites for cost-effective TE applications.

A CrMnFeCoNi high entropy alloy boosting oxygen evolution/reduction reactions and zinc-air battery performance - He, Ren; Yang, Linlin; Zhang, Yu; Wang, Xiang; Lee, Seungho; Zhang, Ting; Li, Lingxiao; Liang, Zhifu; Chen, Jingwei; Li, Junshan; Ostovari Moghaddam, Ahmad; Llorca, Jordi; et al. (Energy Storage Materials)
The development of cost-effective, high-activity and stable bifunctional catalysts for the oxygen reduction and evolution reactions (ORR/OER) is essential for zinc–air batteries (ZABs) to reach the market. Such catalysts must contain multiple adsorption/reaction sites to cope with the high demands of reversible oxygen electrodes. Herein, we propose a high entropy alloy (HEA) based on relatively abundant elements as a bifunctional ORR/OER catalyst. More specifically, we detail the synthesis of a CrMnFeCoNi HEA through a low-temperature solution-based approach. Such HEA displays superior OER performance with an overpotential of 265 mV at a current density of 10 mA/cm2, and a 37.9 mV/dec Tafel slope, well above the properties of a standard commercial catalyst based on RuO2. This high performance is partially explained by the presence of twinned defects, the incidence of large lattice distortions, and the electronic synergy between the different components, being Cr key to decreasing the energy barrier of the OER rate-determining step. CrMnFeCoNi also displays superior ORR performance with a half-potential of 0.78 V and an onset potential of 0.88 V, comparable with commercial Pt/C. The potential gap (Egap) between the OER overpotential and the ORR half-potential of CrMnFeCoNi is just 0.734 V. Taking advantage of these outstanding properties, ZABs are assembled using the CrMnFeCoNi HEA as air cathode and a zinc foil as the anode. The assembled cells provide an open-circuit voltage of 1.489 V, i.e. 90% of its theoretical limit (1.66 V), a peak power density of 116.5 mW/cm2, and a specific capacity of 836 mAh/g that stays stable for more than 10 days of continuous cycling, i.e. 720 cycles @ 8 mA/cm2 and 16.6 days of continuous cycling, i.e. 1200 cycles @ 5 mA/cm2.

Optical and electronic signal stabilization of plasmonic fiber optic gate electrodes: Towards improved real-time dual-mode biosensing - Hasler, Roger; Steger-Polt, Marie Helene; Reiner-Rozman, Ciril; Fossati, Stefan; Lee, Seungho; Aspermair, Patrik; Kleber, Christoph; Ibáñez, Maria; Dostalek, Jakub; Knoll, Wolfgang (Frontiers in Physics)
The use of multimodal readout mechanisms next to label-free real-time monitoring of biomolecular interactions can provide valuable insight into surface-based reaction mechanisms. To this end, the combination of an electrolyte-gated field-effect transistor (EG-FET) with a fiber optic-coupled surface plasmon resonance (FO-SPR) probe serving as gate electrode has been investigated to deconvolute surface mass and charge density variations associated to surface reactions. However, applying an electrochemical potential on such gold-coated FO-SPR gate electrodes can induce gradual morphological changes of the thin gold film, leading to an irreversible blue-shift of the SPR wavelength and a substantial signal drift. We show that mild annealing leads to optical and electronic signal stabilization (20-fold lower signal drift than as-sputtered fiber optic gates) and improved overall analytical performance characteristics. The thermal treatment prevents morphological changes of the thin gold-film occurring during operation, hence providing reliable and stable data immediately upon gate voltage application. Thus, the readout output of both transducing principles, the optical FO-SPR and electronic EG-FET, stays constant throughout the whole sensing time-window and the long-term effect of thermal treatment is also improved, providing stable signals even after 1 year of storage. Annealing should therefore be considered a necessary modification for applying fiber optic gate electrodes in real-time multimodal investigations of surface reactions at the solid-liquid interface.

A 3d‐4d‐5d high entropy alloy as a bifunctional oxygen catalyst for robust aqueous zinc–air batteries - He, Ren; Yang, Linlin; Zhang, Yu; Jiang, Daochuan; Lee, Seungho; Horta, Sharona; Liang, Zhifu; Lu, Xuan; Ostovari Moghaddam, Ahmad; Li, Junshan; Ibáñez, Maria; Xu, Ying; et al. (Advanced Materials)
High entropy alloys (HEAs) are highly suitable candidate catalysts for oxygen evolution and reduction reactions (OER/ORR) as they offer numerous parameters for optimizing the electronic structure and catalytic sites. Herein, FeCoNiMoW HEA nanoparticles are synthesized using a solution‐based low‐temperature approach. Such FeCoNiMoW nanoparticles show high entropy properties, subtle lattice distortions, and modulated electronic structure, leading to superior OER performance with an overpotential of 233 mV at 10 mA cm −2 and 276 mV at 100 mA cm −2 . Density functional theory calculations reveal the electronic structures of the FeCoNiMoW active sites with an optimized d‐band center position that enables suitable adsorption of OOH* intermediates and reduces the Gibbs free energy barrier in the OER process. Aqueous zinc–air batteries (ZABs) based on this HEA demonstrate a high open circuit potential of 1.59 V, a peak power density of 116.9 mW cm −2 , a specific capacity of 857 mAh g Zn −1 , and excellent stability for over 660 h of continuous charge–discharge cycles. Flexible and solid ZABs are also assembled and tested, displaying excellent charge–discharge performance at different bending angles. This work shows the significance of 4d/5d metal‐modulated electronic structure and optimized adsorption ability to improve the performance of OER/ORR, ZABs, and beyond.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Defect engineering in solution-processed polycrystalline SnSe leads to high thermoelectric performance - Liu, Yu; Calcabrini, Mariano; Yu, Yuan; Lee, Seungho; Chang, Cheng; David, Jérémy; Ghosh, Tanmoy; Spadaro, Maria Chiara; Xie, Chenyang; Cojocaru-Mirédin, Oana; Arbiol, Jordi; Ibáñez, Maria (ACS Nano)
SnSe has emerged as one of the most promising materials for thermoelectric energy conversion due to its extraordinary performance in its single-crystal form and its low-cost constituent elements. However, to achieve an economic impact, the polycrystalline counterpart needs to replicate the performance of the single crystal. Herein, we optimize the thermoelectric performance of polycrystalline SnSe produced by consolidating solution-processed and surface-engineered SnSe particles. In particular, the SnSe particles are coated with CdSe molecular complexes that crystallize during the sintering process, forming CdSe nanoparticles. The presence of CdSe nanoparticles inhibits SnSe grain growth during the consolidation step due to Zener pinning, yielding a material with a high density of grain boundaries. Moreover, the resulting SnSe–CdSe nanocomposites present a large number of defects at different length scales, which significantly reduce the thermal conductivity. The produced SnSe–CdSe nanocomposites exhibit thermoelectric figures of merit up to 2.2 at 786 K, which is among the highest reported for solution-processed SnSe.
Keywords: tin selenide; nanocomposite; grain growth; Zener pinning; thermoelectricity; annealing; solution processing

Field-effect transistor with a plasmonic fiber optic gate electrode as a multivariable biosensor device - Hasler, Roger; Reiner-Rozman, Ciril; Fossati, Stefan; Aspermair, Patrik; Dostalek, Jakub; Lee, Seungho; Ibáñez, Maria; Bintinger, Johannes; Knoll, Wolfgang (ACS Sensors)
A novel multivariable system, combining a transistor with fiber optic-based surface plasmon resonance spectroscopy with the gate electrode simultaneously acting as the fiber optic sensor surface, is reported. The dual-mode sensor allows for discrimination of mass and charge contributions for binding assays on the same sensor surface. Furthermore, we optimize the sensor geometry by investigating the influence of the fiber area to transistor channel area ratio and distance. We show that larger fiber optic tip diameters are favorable for electronic and optical signals and demonstrate the reversibility of plasmon resonance wavelength shifts after electric field application. As a proof of principle, a layer-by-layer assembly of polyelectrolytes is performed to benchmark the system against multivariable sensing platforms with planar surface plasmon resonance configurations. Furthermore, the biosensing performance is assessed using a thrombin binding assay with surface-immobilized aptamers as receptors, allowing for the detection of medically relevant thrombin concentrations.

Field-effect transistor with a plasmonic fiber optic gate electrode as a multivariable biosensor device - Hasler, Roger; Reiner-Rozman, Ciril; Fossati, Stefan; Aspermair, Patrik; Dostalek, Jakub; Lee, Seungho; Ibáñez, Maria; Bintinger, Johannes; Knoll, Wolfgang
Detailed information about the data set see "dataset description.txt" file.

The chemistry of Cu₃N and Cu₃PdN nanocrystals - Parvizian, Mahsa; Duràn Balsa, Alejandra; Pokratath, Rohan; Kalha, Curran; Lee, Seungho; Van Den Eynden, Dietger; Ibáñez, Maria; Regoutz, Anna; De Roo, Jonathan (Angewandte Chemie - International Edition)
The precursor conversion chemistry and surface chemistry of Cu3N and Cu3PdN nanocrystals are unknown or contested. Here, we first obtain phase-pure, colloidally stable nanocubes. Second, we elucidate the pathway by which copper(II) nitrate and oleylamine form Cu3N. We find that oleylamine is both a reductant and a nitrogen source. Oleylamine is oxidized by nitrate to a primary aldimine, which reacts further with excess oleylamine to a secondary aldimine, eliminating ammonia. Ammonia reacts with CuI to form Cu3N. Third, we investigated the surface chemistry and find a mixed ligand shell of aliphatic amines and carboxylates (formed in situ). While the carboxylates appear tightly bound, the amines are easily desorbed from the surface. Finally, we show that doping with palladium decreases the band gap and the material becomes semi-metallic. These results bring insight into the chemistry of metal nitrides and might help the development of other metal nitride nanocrystals.

Surface functionalization of surfactant-free particles: A strategy to tailor the properties of nanocomposites for enhanced thermoelectric performance - Chang, Cheng; Liu, Yu; Lee, Seungho; Spadaro, Maria; Koskela, Kristopher M.; Kleinhanns, Tobias; Costanzo, Tommaso; Arbiol, Jordi; Brutchey, Richard L.; Ibáñez, Maria (Angewandte Chemie - International Edition)
The broad implementation of thermoelectricity requires high-performance and low-cost materials. One possibility is employing surfactant-free solution synthesis to produce nanopowders. We propose the strategy of functionalizing “naked” particles’ surface by inorganic molecules to control the nanostructure and, consequently, thermoelectric performance. In particular, we use bismuth thiolates to functionalize surfactant-free SnTe particles’ surfaces. Upon thermal processing, bismuth thiolates decomposition renders SnTe-Bi2S3 nanocomposites with synergistic functions: 1) carrier concentration optimization by Bi doping; 2) Seebeck coefficient enhancement and bipolar effect suppression by energy filtering; and 3) lattice thermal conductivity reduction by small grain domains, grain boundaries and nanostructuration. Overall, the SnTe-Bi2S3 nanocomposites exhibit peak z T up to 1.3 at 873 K and an average z T of ≈0.6 at 300–873 K, which is among the highest reported for solution-processed SnTe.

Solution-processed inorganic thermoelectric materials: Opportunities and challenges ∇ - Fiedler, Christine; Kleinhanns, Tobias; Garcia, Maria; Lee, Seungho; Calcabrini, Mariano; Ibáñez, Maria (Chemistry of Materials)
Thermoelectric technology requires synthesizing complex materials where not only the crystal structure but also other structural features such as defects, grain size and orientation, and interfaces must be controlled. To date, conventional solid-state techniques are unable to provide this level of control. Herein, we present a synthetic approach in which dense inorganic thermoelectric materials are produced by the consolidation of well-defined nanoparticle powders. The idea is that controlling the characteristics of the powder allows the chemical transformations that take place during consolidation to be guided, ultimately yielding inorganic solids with targeted features. Different from conventional methods, syntheses in solution can produce particles with unprecedented control over their size, shape, crystal structure, composition, and surface chemistry. However, to date, most works have focused only on the low-cost benefits of this strategy. In this perspective, we first cover the opportunities that solution processing of the powder offers, emphasizing the potential structural features that can be controlled by precisely engineering the inorganic core of the particle, the surface, and the organization of the particles before consolidation. We then discuss the challenges of this synthetic approach and more practical matters related to solution processing. Finally, we suggest some good practices for adequate knowledge transfer and improving reproducibility among different laboratories.
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

Exploiting the lability of metal halide perovskites for doping semiconductor nanocomposites - Calcabrini, Mariano; Genc, Aziz; Liu, Yu; Kleinhanns, Tobias; Lee, Seungho; Dirin, Dmitry N.; Akkerman, Quinten A.; Kovalenko, Maksym V.; Arbiol, Jordi; Ibáñez, Maria (ACS Energy Letters)
Cesium lead halides have intrinsically unstable crystal lattices and easily transform within perovskite and nonperovskite structures. In this work, we explore the conversion of the perovskite CsPbBr3 into Cs4PbBr6 in the presence of PbS at 450 °C to produce doped nanocrystal-based composites with embedded Cs4PbBr6 nanoprecipitates. We show that PbBr2 is extracted from CsPbBr3 and diffuses into the PbS lattice with a consequent increase in the concentration of free charge carriers. This new doping strategy enables the adjustment of the density of charge carriers between 1019 and 1020 cm–3, and it may serve as a general strategy for doping other nanocrystal-based semiconductors.

The importance of surface adsorbates in solution‐processed thermoelectric materials: The case of SnSe - Liu, Yu; Calcabrini, Mariano; Yu, Yuan; Genç, Aziz; Chang, Cheng; Costanzo, Tommaso; Kleinhanns, Tobias; Lee, Seungho; Llorca, Jordi; Cojocaru‐Mirédin, Oana; Ibáñez, Maria (Advanced Materials)
Solution synthesis of particles emerged as an alternative to prepare thermoelectric materials with less demanding processing conditions than conventional solid-state synthetic methods. However, solution synthesis generally involves the presence of additional molecules or ions belonging to the precursors or added to enable solubility and/or regulate nucleation and growth. These molecules or ions can end up in the particles as surface adsorbates and interfere in the material properties. This work demonstrates that ionic adsorbates, in particular Na⁺ ions, are electrostatically adsorbed in SnSe particles synthesized in water and play a crucial role not only in directing the material nano/microstructure but also in determining the transport properties of the consolidated material. In dense pellets prepared by sintering SnSe particles, Na remains within the crystal lattice as dopant, in dislocations, precipitates, and forming grain boundary complexions. These results highlight the importance of considering all the possible unintentional impurities to establish proper structure-property relationships and control material properties in solution-processed thermoelectric materials.
Keywords: mechanical engineering; mechanics of materials; general materials science

Influence of copper telluride nanodomains on the transport properties of n-type bismuth telluride - Zhang, Yu; Xing, Congcong; Liu, Yu; Li, Mengyao; Xiao, Ke; Guardia, Pablo; Lee, Seungho; Han, Xu; Moghaddam, Ahmad; Roa, Joan J; Arbiol, Jordi; Ibáñez, Maria; et al. (Chemical Engineering Journal)
The high processing cost, poor mechanical properties and moderate performance of Bi2Te3–based alloys used in thermoelectric devices limit the cost-effectiveness of this energy conversion technology. Towards solving these current challenges, in the present work, we detail a low temperature solution-based approach to produce Bi2Te3-Cu2-xTe nanocomposites with improved thermoelectric performance. Our approach consists in combining proper ratios of colloidal nanoparticles and to consolidate the resulting mixture into nanocomposites using a hot press. The transport properties of the nanocomposites are characterized and compared with those of pure Bi2Te3 nanomaterials obtained following the same procedure. In contrast with most previous works, the presence of Cu2-xTe nanodomains does not result in a significant reduction of the lattice thermal conductivity of the reference Bi2Te3 nanomaterial, which is already very low. However, the introduction of Cu2-xTe yields a nearly threefold increase of the power factor associated to a simultaneous increase of the Seebeck coefficient and electrical conductivity at temperatures above 400 K. Taking into account the band alignment of the two materials, we rationalize this increase by considering that Cu2-xTe nanostructures, with a relatively low electron affinity, are able to inject electrons into Bi2Te3, enhancing in this way its electrical conductivity. The simultaneous increase of the Seebeck coefficient is related to the energy filtering of charge carriers at energy barriers within Bi2Te3 domains associated with the accumulation of electrons in regions nearby a Cu2-xTe/Bi2Te3 heterojunction. Overall, with the incorporation of a proper amount of Cu2-xTe nanoparticles, we demonstrate a 250% improvement of the thermoelectric figure of merit of Bi2Te3.

Ligand-mode directed selectivity in Cu-Ag core-shell based gas diffusion electrodes for CO2 electroreduction - Irtem, Erdem; Arenas Esteban, Daniel; Duarte, Miguel; Choukroun, Daniel; Lee, Seungho; Ibáñez, Maria; Bals, Sara; Breugelmans, Tom (ACS Catalysis)
Bimetallic nanoparticles with tailored size and specific composition have shown promise as stable and selective catalysts for electrochemical reduction of CO2 (CO2R) in batch systems. Yet, limited effort was devoted to understand the effect of ligand coverage and postsynthesis treatments on CO2 reduction, especially under industrially applicable conditions, such as at high currents (>100 mA/cm2) using gas diffusion electrodes (GDE) and flow reactors. In this work, Cu–Ag core–shell nanoparticles (11 ± 2 nm) were prepared with three different surface modes: (i) capped with oleylamine, (ii) capped with monoisopropylamine, and (iii) surfactant-free with a reducing borohydride agent; Cu–Ag (OAm), Cu–Ag (MIPA), and Cu–Ag (NaBH4), respectively. The ligand exchange and removal was evidenced by infrared spectroscopy (ATR-FTIR) analysis, whereas high-resolution scanning transmission electron microscopy (HAADF-STEM) showed their effect on the interparticle distance and nanoparticle rearrangement. Later on, we developed a process-on-substrate method to track these effects on CO2R. Cu–Ag (OAm) gave a lower on-set potential for hydrocarbon production, whereas Cu–Ag (MIPA) and Cu–Ag (NaBH4) promoted syngas production. The electrochemical impedance and surface area analysis on the well-controlled electrodes showed gradual increases in the electrical conductivity and active surface area after each surface treatment. We found that the increasing amount of the triple phase boundaries (the meeting point for the electron–electrolyte–CO2 reactant) affect the required electrode potential and eventually the C+2e̅/C2e̅ product ratio. This study highlights the importance of the electron transfer to those active sites affected by the capping agents—particularly on larger substrates that are crucial for their industrial application.